Kidney stone characteristics in diabetics versus nondiabetics at a tertiary care center in Saudi Arabia - Ibrahim Basem Nafadi; Abdullah Ahmed Alsulami; Nawaf Faisal Halabi; Abdulrahman Abdullah Alsubhi; Sami Wessam Maghrabi; Waleed Saad Alshehri; Majed Ramadan; Anwar Khan; Suhaib Radi (Urology Annals)
Background: Kidney stones can significantly impact individuals, but existing literature often overlooks the comprehensive effects by not considering the various factors such as stone size, presence of obstruction, and treatment methods, among those with and without diabetes. This study seeks to explore the relationship between diabetes and kidney stone formation, addressing these gaps in research. Methodology: This cross-sectional study assesses the diverse impacts of kidney stones on adults diagnosed with type 2 diabetes mellitus and nondiabetic adults from 2019 to 2022 in Jeddah, Saudi Arabia. Institutional review board approval was secured for this research. Data collection occurred from December 1, 2022, to March 1, 2023, and the analysis was performed using SPSS software. Results: The study included 254 adults diagnosed with kidney stones, 127 with type 2 diabetes, and 127 nondiabetics. Our study showed that the individuals with diabetes were more likely to have larger kidney stones than those without diabetes (13.12 mm vs. 10.53 mm, P = 0.03). Moreover, individuals with hypertension and dyslipidemia also had significantly larger stones. However, no significant difference was found between the two groups regarding the presence of obstruction and the treatment modality. Conclusion: This study revealed that in Saudi Arabia, individuals with diabetes who also suffer from kidney stones tend to develop larger stones. In addition, these individuals frequently exhibit other comorbid conditions, including hypertension, dyslipidemia, obesity, and renal disease. The significance of these findings may inform future strategies for both primary and secondary prevention of kidney stones in diabetic patients.